2004
DOI: 10.2214/ajr.183.2.1830283
|View full text |Cite
|
Sign up to set email alerts
|

Does CT of Thymic Epithelial Tumors Enable Us to Differentiate Histologic Subtypes and Predict Prognosis?

Abstract: Although CT is of limited value in differentiating histologic subtypes according to the WHO classification, CT findings may serve as predictors of postoperative recurrence or metastasis for the thymic epithelial tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
163
2
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(207 citation statements)
references
References 25 publications
20
163
2
22
Order By: Relevance
“…In a review of 200 patients with thymic epithelial tumors, 5-year survival rates of each subtype of WHO classification were 100% in type A thymoma, 100% in type AB, 94.1% in type B1, 75.0% in type B2, and 70.0% in type B3, and 48.0% in thymic carcinoma (33). On the basis of significant correlation of the WHO histological classification and prognosis, the thymic epithelial tumors can be divided into three main groups; low-risk thymomas (types A, AB, B1), high-risk thymomas (types B2 and B3), and thymic carcinomas (35).…”
Section: Who Classification Of Thymic Epithelial Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 200 patients with thymic epithelial tumors, 5-year survival rates of each subtype of WHO classification were 100% in type A thymoma, 100% in type AB, 94.1% in type B1, 75.0% in type B2, and 70.0% in type B3, and 48.0% in thymic carcinoma (33). On the basis of significant correlation of the WHO histological classification and prognosis, the thymic epithelial tumors can be divided into three main groups; low-risk thymomas (types A, AB, B1), high-risk thymomas (types B2 and B3), and thymic carcinomas (35).…”
Section: Who Classification Of Thymic Epithelial Tumorsmentioning
confidence: 99%
“…Jeong et al (35) correlated CT findings of thymic epithelial tumors with WHO histopathologic subtypes. Lobulated contour was more often seen in high-risk thymomas (types B2 and B3) and thymic carcinomas than in low-risk thymomas (types A, AB, and B1).…”
Section: Who Classification Of Thymic Epithelial Tumorsmentioning
confidence: 99%
“…However, conventional imaging modalities may be unable to differentiate among the various WHO histologic subtypes [3]. Recently, several studies were reported regarding the clinical role of positron emission tomography (PET) or PET/computed tomography (CT) in the evaluation of thymic epithelial tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Thymic epithelial tumors usually can be assessed with computed tomography (CT) and magnetic resonance imaging (MRI) [1,2]. Morphologic features are used for characterizing thymic lesions, such as the contours and shapes of the lesions, the presence of necrosis, calcification, mediastinal fat or great vessel invasion, contrast enhancement, and adjacent lymph node enlargement.…”
mentioning
confidence: 99%